The effect of transglutaminase-2 inhibitor on pulmonary vascular remodeling in rats with pulmonary arterial hypertension - Ting Wang; Yan Duan; Dong Liu; Gang Li; Bin Liu (Clinical and Experimental Hypertension, 2022)
To investigate the relationship between transglutaminase type 2 (TG2) and pulmonary vascular remodeling in the formation of pulmonary arterial hypertension (PAH), and to investigate the effect of the inhibitor cystamine dihydrochloride on pulmonary vascular remodeling in rats with PAH. Thirty healthy male Sprague Dawley rats were randomly divided into a control group, a PAH model group, and an intervention group. The mean pulmonary artery pressure (mPAP), the right ventricular hypertrophy index (RVHI), the percentage wall thickness of the pulmonary artery (WT%), and the degree of neointimal proliferation were measured, and the pathological changes in the pulmonary tissues were observed.Messenger ribonucleic acid (mRNA) and protein expressions of TG2, 5-hydroxytryptamine transporter (5-HTT), and Rho-associated protein kinase 2 (ROCK2) in the pulmonary tissues of the three groups of rats were detected. Compared with the control group, the mPAP, RVHI, and WT% were significantly higher in the model group, the degree of neointimal proliferation was significantly increased, and the mRNA and protein expressions of TG2, 5-HTT, and ROCK2 in the pulmonary tissue were significantly increased. Compared with the model group, the mPAP, RVHI, WT%, and the degree of neointimal proliferation were significantly lower in the intervention group, as were the mRNA and protein expressions of TG2, 5-HTT, and ROCK2 in the pulmonary tissue. The TG2 inhibitor cystamine dihydrochloride can prevent the formation of PAH to some extent. This might be due to the inhibition of the TG2 activity, 5-HTT expression, and possibly the inhibition of RhoA/ROCK signaling pathway activation.